2012
DOI: 10.1158/0008-5472.can-11-2848
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase and the Canonical Wnt Pathway Protect Lung Cancer Cells from EGFR Inhibition

Abstract: Lung cancer is the leading cause of death worldwide. Adenocarcinomas, the most common histological subtype of non-small cell lung cancer (NSCLC), are frequently associated with activating mutations in the epidermal growth factor receptor (EGFR) gene. Although these patients often respond clinically to the EGFR tyrosine kinase inhibitors erlotinib and gefitinib, relapse inevitably occurs, suggesting the development of escape mechanisms that promote cell survival. Using a loss-of-function, whole genome shRNA scr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
117
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 47 publications
3
117
0
2
Order By: Relevance
“…These inhibitors used in combined therapy with paclitaxel resulted in an increased apoptotic response in comparison with single inhibitor or paclitaxel treatment, even in PKCd-silenced cells. Supporting our results, other authors showed that the inhibition of these pathways improved the apoptotic response to EGFR-targeting therapy in lung cancer (28), deguelin and microtubule-targeting drugs in prostate cancer (29,31), paclitaxel and irinotecan in colon cancer (30), or tamoxifen in glioma cells (24).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These inhibitors used in combined therapy with paclitaxel resulted in an increased apoptotic response in comparison with single inhibitor or paclitaxel treatment, even in PKCd-silenced cells. Supporting our results, other authors showed that the inhibition of these pathways improved the apoptotic response to EGFR-targeting therapy in lung cancer (28), deguelin and microtubule-targeting drugs in prostate cancer (29,31), paclitaxel and irinotecan in colon cancer (30), or tamoxifen in glioma cells (24).…”
Section: Discussionsupporting
confidence: 88%
“…On the basis of these articles, we propose that PKCd would modulate Mcl-1 by regulation of the Wnt/b-catenin pathway in prostate cancer cells. The Wnt/b-catenin pathway regulates embryogenesis, proliferation, cell differentiation, or migration, and it is abnormally activated in different tumor types (18,20,23,24,28,29). b-catenin is a strongly regulated factor with a central role in this pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a combination of an EGFR and Tankyrase inhibition recently revealed a close functional correlation of both pathways and confirmed the synergistic effect of a dual antagonistic treatment in lung cancer cells [477]. Zibotentan, a ET(A)R antagonist when combined with the EGFR inhibitor gefitinib, reduces -catenin activity [387].…”
Section: Discussionmentioning
confidence: 79%
“…The common hallmark in various human caner tissues is the nuclear retention of β-catenin, the main effector of the canonical Wnt signaling pathway (Fodde et al, 2001;Casás-Selves et al, 2012). In the absence of Wnt ligands, β-catenin is tightly regulated by a multi-protein complex including: the tumour suppressor APC, the scaffolding protein axin, and the phosphokinases GSK-3β and CK1 (Fodde et al, 2001;Casás-Selves et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of Wnt ligands, β-catenin is tightly regulated by a multi-protein complex including: the tumour suppressor APC, the scaffolding protein axin, and the phosphokinases GSK-3β and CK1 (Fodde et al, 2001;Casás-Selves et al, 2012). Upon ligand activation, the complex is destabilized, allowing for cytoplasmic β-catenin accumulation with subsequent nuclear translocation (Fodde et al, 2001;Moon et al, 2004).…”
Section: Discussionmentioning
confidence: 99%